Accumulation and deposition of triacylglycerols in the starchy endosperm of wheat grain. (March 2021) - González-Thuillier, Irene; Pellny, Till K.; Tosi, Paola; Mitchell, Rowan A.C.; Haslam, Richard; Shewry, Peter R.
Abstract: A combination of lipidomics, transcriptomics and bioimaging has been used to study triacylglycerol synthesis and deposition in the developing starchy endosperm of wheat. The content of TAG increased between 14 and 34 days after anthesis, from 50 to 115 mg/100 g dry wt and from about 35 to 175 mg/100 g dry wt in two experiments. The major fatty acids were C16 (palmitic C16:0 and palmitoleic C16:1) and C18 (stearic C18:0, oleic C18:1, linoleic C18:2 and linolenic C18:3), with unsaturated fatty acids accounting for about 75–80% of the total throughout development. Linoleic acid (C18:2) was the major component at all stages and the proportion increased during development. Transcript profiling indicated that predominant route to TAG synthesis and oil accumulation is via the Kennedy pathway and diacylglycerol acyltransferase (DGAT) activity. Confocal microscopy of stained tissue sections showed that TAG accumulated in droplets which are associated with protein and concentrated in the starchy endosperm cells below the sub-aleurone cells. Transcripts encoding 16kd oleosins were also expressed, indicating that the oil droplets are in part stabilised by oleosin proteins. Graphical abstract: Image 1 Highlights: Integrated study of triacylglycerol synthesis and deposition in wheat endosperm. First lipidomic analysis of triacylglycerol composition in wheat starchy endosperm. Bioimaging of lipid deposition in starchy endosperm cells. Transcriptome analysis shows operation of Kennedy pathway for lipid synthesis.